Focusing on feedback: How nurse practitioners can use focus group interviews to build a patient‐centered practice. Issue 9 (22nd August 2013) - Pozzar, Rachel A.; Allen, Nancy A.; Stamp, Kelly D.; Sampson, Deborah A.
Abstract Purpose The success or failure of clinical interventions often rests upon the degree of insight nurse practitioners (NPs) have into their patients' preferences for receiving their care. Therefore, NPs have a vested interest in understanding the perspective of their patients, which can be derived by conducting practice‐specific focus groups. This article offers NPs practice guidelines for conducting focus groups to improve practice and quality and making practice‐related decisions. Data sources An extensive review of the scholarly databases and scientific literature. Conclusions Focus groups can generate valuable data for NPs in clinical practice settings. Currently, focus groups are rarely used for this purpose; however, data gathered from the population served could be invaluable for improving practice, quality, and decisions made regarding the types of services that NPs provide for their patients. Implications for practice The benefits of an NP clinician conducting focus groups are that they provide a forum for listening to the people they serve and learning from them. The knowledge gained from patients allows the NP to tailor their interventions and care to meet the patient's needs, and may be required to make the practice thrive.